FUNGSI PARTAI POLITIK DALAM PENDIDIKAN POLITIK BAGI KAUM MUDA DI KABUPATEN SUMBA BARAT DAYA DITINJAU DARI UNDANG-UNDANG NOMOR 2 TAHUN 2011 TENTANG PARTAI POLITIK - Kota, Adrianus A; Ratu Udju, Hernimus; Ndun, Ivan (Petitum Law Journal, 2025)
This study aims to analyze the function of political parties in providing political education to young people in Southwest Sumba Regency based on Law Number 2 of 2011 concerning Political Parties. Political parties have a strategic role in creating political awareness and increasing the political participation of the younger generation through education, socialization, and political training. In addition, this study also aims to find out and analyze the factors that inhibit the implementation of political party functions in political education for young people. This research is expected to contribute ideas to political parties in Southwest Sumba Regency in carrying out their functions and responsibilities in political education for young people. This research uses a normative juridical method with a legal approach and is supported by empirical studies through interviews with local political party administrators and youth. The research data is sourced from primary, secondary, and tertiary data collected through interview, observation, and literature study techniques. The results of the study show that (1) political parties need to improve political education, socialization, supervision, and cooperation with the community, especially young people, in order to be more effective in providing an understanding of politics. (2) Factors that hinder the implementation of political party functions in political education include ineffective communication, low awareness of young people to participate in politics, political socialization is still minimal, and lack of involvement between political parties and institutions related to political education. Therefore, efforts are needed to strengthen the role of political parties in political education through more structured and sustainable programs in accordance with the mandate of Law Number 2 of 2011 concerning Political Parties.